2006
DOI: 10.1002/pam.20227
|View full text |Cite
|
Sign up to set email alerts
|

Employment, privatization, and managerial choice: Does contracting out reduce public sector employment?

Abstract: We examine the effects of governments ' use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 16 publications
0
57
0
1
Order By: Relevance
“…It has been used to improve the quality of services as well as to reduce the cost of public services. However, Fernandez, Smith, and Wenger (2006) found that contracting out contributes to a drop in full-time employment in the public sector and an increase in part-time public employment. A study on privatization in Germany indicates that members of the public service tend to oppose privatization, because they feel that privatization may reduce the status and role of public service as well as threaten their job security (Legge & Rainey, 2003).…”
Section: Two Types Of Public Administrative Reformmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been used to improve the quality of services as well as to reduce the cost of public services. However, Fernandez, Smith, and Wenger (2006) found that contracting out contributes to a drop in full-time employment in the public sector and an increase in part-time public employment. A study on privatization in Germany indicates that members of the public service tend to oppose privatization, because they feel that privatization may reduce the status and role of public service as well as threaten their job security (Legge & Rainey, 2003).…”
Section: Two Types Of Public Administrative Reformmentioning
confidence: 93%
“…To begin with, contracting-out may have a negative impact on the trust in management. Public employees are dissatisfied with reduction of their role in public service, because privatization decreases the number of services directly provided by the public division (Fernandez et al, 2006).…”
Section: Contracting Outmentioning
confidence: 99%
“…Chandler and Feuille (1994) have provided a more sophisticated view on unions showing that adversarial union relations with city management increase the likelihood of contracting out when compared to no union at all; conversely, cooperative relations between union and city have the opposite effect. Finally, Fernandez, Smith, and Wenger (2007) decompose public employees and find that contracting public services to the for‐profit sector generates a decrease in full‐time public employment but an increase in part‐time employment.…”
Section: Theorymentioning
confidence: 99%
“…The author later on mentioned that the challenges of outsourcing such as, the need for public sector organisations to measure performance, administer contracts and determine levels of responsibility or accountability can translate into high costs for the local authorities. Fernandez et al (2012) highlighted that the argument for outsourcing of public services has clear disadvantages for the magnitude of the public workforce and public employment in that it reduces it. Outsourcing functions to the private sector saves money most of the time and most of the savings tend to disadvantage the employees of the local authorities.…”
Section: Financial Implications Of Outsourcing On Lasmentioning
confidence: 99%